Exploring How Students Utilize and Perceive Artificial Intelligence in Academic Writing: A Qualitative Study - Ningsih, Febri Wahyu; Dangin, Dangin (Journal of English Language and Education, 2026)
The development of Artificial Intelligence (AI) has driven substantial transformations in educational methodologies in higher education, particularly in Student Academic Writing. This study seeks to examine students' use of AI in academic writing assignments and to identify related opportunities and constraints. The study employed a descriptive qualitative methodology, involving five students from the English Language Education Research Program selected using a purposive sampling strategy. Data were obtained through semi-structured interviews and evaluated thematically, concentrating on two main themes: the uses and potential of AI, and concerns and barriers related to its implementation. The findings indicate that students use AI as a pedagogical aid for brainstorming ideas, understanding complex topics, and organizing academic writing, without replacing critical thinking processes. Students also believe that AI can foster a mind-safe learning environment and help people learn faster. The study also raises concerns about the authenticity of information, the possibility of plagiarism, and students' over-reliance on AI, which may undermine their ability to think independently and independently. Therefore, this study demonstrates that AI has significant potential in improving students' academic writing when used critically, ethically, and thoughtfully, complemented by digital literacy and appropriate pedagogical supervision to maintain academic integrity.